Do Family Members of Dialysis Patients Have a Positive Attitude Toward Organ Donation? - Tumin, M.; Tafran, K.; Zakaria, R.H.; Satar, N.M.; Ng, K.P.; Lim, S.K. (Springer Verlag (Germany), 2015)
Background: Malaysia, which currently uses the informed consent system (ICS), is suffering from a severe shortage of organs for transplantation. Family members of dialysis patients (FMDPs) are expected to have a positive attitude toward deceased organ donation (DOD) because they have a close relative in need of a kidney donation. This study explores FMDPs' attitude toward DOD under the ICS and the presumed consent system (PCS). Material/Methods: The attitude of 350 FMDPs toward DOD under the ICS and PCS were sought between June and October 2013 in 3 dialysis institutions in Kuala Lumpur, Malaysia. Results: Under the ICS, 6.6% of respondents were registered donors, 6.6% were ready to register at the time of the survey, 38.6% were willing to donate but not ready to register at the time of the survey, and 48.2% were unwilling to donate organs upon death. If the PCS were implemented, 57.7% of respondents (28.7% of the willing donors and 88.7% of the unwilling respondents) stated that they would officially object to organ donation. Conclusions: FMDPs' attitude toward DOD is not more positive or significantly better than that of the general public (based on earlier studies). The PCS may increase the number of donors, but it may also worsen the attitude of FMDPs toward DOD. Strategies aiming to promote DOD in Malaysia should be revised, and should perhaps be focused on enhancing trust of the medical system.